Regional Disparities of Social and Demographic Indicators in Morocco: A Comparative Cartographic Analysis Between the 2014 and 2024 Censuses - Akallouch, Adil; Hamjik , Mohamed; Mahjoub, Aziz; Boudilab, Hossain (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This article aims to analyze the regional disparities of social and de-mographic indicators in Morocco by conducting a comparative carto-graphic study between the 2014 and 2024 censuses. Using data from the General Population and Housing Census (RGPH) and reports from the High Commission for Planning, combined with Geographic Infor-mation Systems (GIS), this research highlights significant spatial and temporal changes across various regions. Key indicators analyzed include population density, unemployment rates, urbanization levels, literacy rates, and economic activity. The results reveal stark regional disparities, with Casablanca-Settat and Tangier-Tetouan-Al Hoceima maintaining high population density and urbanization growth, while rural regions like Drâa-Tafilalet and Béni Mellal-Khénifra continue to face persistent challenges, such as high unemployment and illiteracy rates. Notably, the southern regions of Laâyoune-Sakia El Hamra and Dakhla-Oued Ed-Dahab have shown remarkable improvements in urbanization and economic activity due to targeted government-led development projects.Quantitatively, the study identifies a 5.4% national increase in ur-banization rates over the past decade, accompanied by a 7% reduc-tion in national illiteracy rates. However, unemployment remains a critical issue, with some regions experiencing only marginal im-provements. The ARIMA model projections indicate further urbaniza-tion by 2030, with potential risks of growing disparities if regional development policies are not effectively implemented. These findings underscore the urgent need for targeted policies aimed at promoting regional equity by investing in education, enhancing job opportuni-ties in rural areas, and fostering balanced urban growth. The study emphasizes the importance of integrating GIS-based spatial analysis into policy-making to ensure sustainable and inclusive development.